SOSTENIBILIDAD DE LAS PRÁCTICAS AGROPECUARIAS DE LA AGRICULTURA FAMILIAR PRODUCTORA DE MAÍZ VERDE DE CÁCERES, BRASIL - Scheuer, Junior Miranda; Neves, Jucimar Ferreira; Neves, Sandra Mara Alves da Silva; Seabra Junior, Santino; Galvanin, Edinéia Aparecida dos Santos [UNESP] (My University, 2021)
Brazilian family farming is essential for the country’s socioeconomic development, but requires evaluations for the identification of environmental impacts and the proposal of sustainable rural development strategies. The objective of this study was to evaluate the sustainability of the agricultural practices of family farming that produces green corn in the municipality of Caceres, department of Mato Grosso, Brazil. The qualitative research is characterized as an exploratory and descriptive case study, carried out through semi-structured interviews with 13 members of family farmers during the 2014/2015 harvest. For the study of sustainability, the Driving Force-State-Response model was used, organized around human, social, physical and natural capital. Human, social, physical and natural capital are interconnected and the strengthening of one will cause, in a chain, the consolidation of the others, in the same way that the weakening of one of the capitals will trigger weaknesses in the others. Thus, the analyses pointed to a situation of compromised sustainability, and the indicators with a negative aspect show an alert about the problem and require joint planning of actions between the actors, while the indicators with positive aspects must be reinforced and valued. The committed sustainability can be repaired/optimized through public policies of national, departmental and municipal, and by actions from local institutional, but development will occur when there is a particular effort of family farming to seek alternatives and break the state, many times, of dependence on the decisions of politicians and officials at different levels of government. However, there is a lack of a society, community leaders, representatives of organizations, executive, and legislative powers (local) that are more proactive, and oriented by the primordial needs of family farming, thus seeking, sustainable rural development.
Sustainability of the agricultural practices of family farming that produces green corn in Caceres, Brazil
Keywords: Brazil; driving force-state-response; Family farming; human capital; natural capital; physical capital; rural development; social capital